ISSUES REGARDING THE IMPROVEMENT OF THE INDIRECT TAXES MECHANISM - Sh.N.Gʻafforov; E.F.Gadoyev (Web of Journals Publishing, 2024)
In this article, a comprehensive study of the mechanism of taxation of indirect taxes, a scientific proposal for improving the mechanism of taxation and effective tax administration and practical recommendations are highlighted.
Keywords: State budget, tax burden, tax rate, solvency, direct and indirect taxes, value added tax, excise and customs duties, economic growth.